Formulation and Evaluation of Physical Stability Natural Acne Gel Based on Aloevera Gel with Essential Oil Blend - Sucia Rahmadani Nurlaila; Ayu Desi Rachmadani; Kun Harismah (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the formulation and evaluation of natural acne gel preparations made from aloe vera gel with a mixture of essential oils where the concentration of aloe vera gel can affect the stability of natural acne gel preparations. The use of herbal cosmetics is preferred because it comes from natural ingredients, is safe, can be used by all skin types, has various choices, is inexpensive, has low side effects, and does not pollute the environment. Organoleptic Test Process, pH Test, Adhesion Test, Spreadability Test, Stability Test (Cycling Test) for evaluation of natural acne gel preparations. The results showed that the higher the concentration of aloe vera gel, the higher the pH, dispersion, and stability. By paying attention to the data from each formula, it can be concluded that the most optimal preparation is the F3 preparation which shows the appropriate pH results, appropriate dispersion and homogeneous stability.